ADAPTING TO CHANGE: THE IMPACT OF MULTIMEDIA LEARNING TOOLS ON HIGHER EDUCATION STUDENTS - Nurul Izzah Mohamad Ghozali; Hapini Awang; Nur Suhaili Mansor; Ramlan Mustapha, (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2024)
This study investigates the impact of multimedia learning tools on higher education students, focusing on their adaptability to change and overall academic performance. In the evolving education landscape, multimedia tools such as interactive videos, digital simulations, and online collaborative platforms are increasingly integrated into curricula to enhance learning experiences. Through a mixed-methods approach, this research combines quantitative data from surveys and academic performance metrics with qualitative insights from student interviews and focus groups. The findings reveal that multimedia tools significantly improve student engagement, comprehension, and retention of complex concepts, fostering a more adaptable and resilient learning environment. Moreover, the study highlights the challenges and limitations students and educators face in adopting these technologies, including accessibility issues, technological proficiency, and the need for continuous pedagogical innovation. The results underscore the transformative potential of multimedia learning tools in higher education, advocating for their strategic implementation to support dynamic and effective learning outcomes.